Strengthening Digital Literacy and Hoax Awareness of SDN Pandean 1 Students - Tri Lestari; Dimas Widya B. Putra; Safira H. Prasetyo; Soffi Setyaningtyas; Nadilla R. Agustin; Nimas A. Rahayuningsih; Ernia T. Asriani; Reza Ramadhani; Siti Zanuba N. Maryam; Roihan B. Perdana; Sai B. Daniel; Welly Mahardhika (Universitas Negeri Semarang, 2026)
This community service-based study responds to the urgency of strengthening digital literacy and awareness of hoaxes among elementary school students amid the increasing use of gadgets. The rapid penetration of digital technology has made children active internet users, but without adequate critical thinking skills, they remain vulnerable to false information and unethical digital behavior. This Program was held at SDN Pandean 1 and involved students in grades IV–VI through structured digital literacy socialization activities that focused on responsible use of gadgets, basic fact verification skills, and digital ethics. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews with students and teachers, and documentation during program Implementation. The findings suggest that although students demonstrate high technical expertise in using digital devices, their ability to critically evaluate information, especially in identifying hoaxes, is still limited. However, such socialization activities contribute to increased awareness in verifying the source of information, recognizing misleading content, and adopting more ethical online behavior. This community service initiative highlights the importance of integrating digital literacy education into elementary learning environments. The results suggest that collaborative involvement between schools, teachers, and parents is essential to build students’ critical digital competencies from an early age.